2019
DOI: 10.1002/epi4.12297
|View full text |Cite
|
Sign up to set email alerts
|

A genome‐wide association study of sodium levels and drug metabolism in an epilepsy cohort treated with carbamazepine and oxcarbazepine

Abstract: Summary Objective To ascertain the clinical and genetic factors contributing to carbamazepine‐ and oxcarbazepine‐induced hyponatremia (COIH), and to carbamazepine (CBZ) metabolism, in a retrospectively collected, cross‐sectional cohort of people with epilepsy. Methods We collected data on serum sodium levels and antiepileptic drug levels in people with epilepsy attending a tertiary epilepsy center while on treatment with CBZ or OXC. We defined hyponatremia as Na+ ≤134 mEq/L. We estimated the CBZ metabolic rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…High serum levels of CBZ or OXC, concomitant use of other ASMs, and being female are risk factors for COIH, as well as age >40 years 5 . A genetic predictor for COIH has not yet been identified 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High serum levels of CBZ or OXC, concomitant use of other ASMs, and being female are risk factors for COIH, as well as age >40 years 5 . A genetic predictor for COIH has not yet been identified 6 …”
Section: Introductionmentioning
confidence: 99%
“…5 A genetic predictor for COIH has not yet been identified. 6 COIH is often assumed to be asymptomatic, but it can lead to symptoms ranging from unsteadiness and mild confusion to acute symptomatic seizures and coma. We found previously that almost half of people with COIH were symptomatic, and in 3% this led to hospital admissions.…”
Section: Introductionmentioning
confidence: 99%
“…Use of other AEDs (dibenzazepine carboxamide AEDs in particular) has also been associated with the occurrence of hyponatremia. For example, a retrospective study of data from 1252 patients treated at tertiary epilepsy referral clinics found that hyponatremia ([Na+] <135 mEq/L) occurred in 57% of patients taking OXC and 32% of patients taking CBZ . Another analysis of 560 adult inpatients at a single center found that hyponatremia occurred in 16% of patients taking CBZ, 43% of patients taking OXC, and 33% of patients taking ESL .…”
Section: Discussionmentioning
confidence: 99%
“…For example, a retrospective study of data from 1252 patients treated at tertiary epilepsy referral clinics found that hyponatremia ([Na+] <135 mEq/L) occurred in 57% of patients taking OXC and 32% of patients taking CBZ. 23 Another analysis of 560 adult inpatients at a single center found that hyponatremia occurred in 16% of patients taking CBZ, 43% of patients taking OXC, and 33% of patients taking ESL. 24 A separate analysis of 1782 patients attending a tertiary epilepsy center found that hyponatremia ([Na+] ≤134 mEq/L) occurred in 26% of patients taking CBZ and 46% of those taking OXC.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al reported that the use of OXC in patients with epilepsy is associated with a dose-dependent reduction in serum sodium levels [ 9 ]. A genetic predictor of OXC-induced hyponatremia has not yet been identified [ 10 ]. During our clinical practice, we have noticed that a longer duration of treatment with OXC could be associated with a higher risk of hyponatremia, therefore, in this study, we aim to evaluate the factors that may increase the risk of OXC-induced hyponatremia.…”
Section: Introductionmentioning
confidence: 99%